2017
DOI: 10.22495/rgcv7i3p1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of external and internal shock in the stability of Indonesia’s financial system

Abstract: The objective of this research is to develop a financial system stability index and analyze the internal and external factors that we expect to affect the stability of the Indonesian financial system. We measured the single model of financial system stability index (FSSI) from year 2004M03 to2014M09 in Indonesia, and compiled a single quantitative measure based on aggregate internal factors and external factors to capture and predict the shocks of the financial system stability. Stability parameters were compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…For instance, Patria Yunita (2022) found that the Islamic Banking Stability Index influences financial stability, highlighting the stability brought about by certain banking practices (Yunita, 2022). Similarly, Maulina Vinus and Suhal Kusairi (2017) reported that banking soundness is a component of financial stability, affirming the positive effect of banking stability on overall financial stability (Vinus & Kusairi, 2017). However, our study advances this understanding by quantifying the specific impact of BSI on FSI and examining additional variables like IR, GDP, and PD in relation to FSI.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 98%
“…For instance, Patria Yunita (2022) found that the Islamic Banking Stability Index influences financial stability, highlighting the stability brought about by certain banking practices (Yunita, 2022). Similarly, Maulina Vinus and Suhal Kusairi (2017) reported that banking soundness is a component of financial stability, affirming the positive effect of banking stability on overall financial stability (Vinus & Kusairi, 2017). However, our study advances this understanding by quantifying the specific impact of BSI on FSI and examining additional variables like IR, GDP, and PD in relation to FSI.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 98%
“…Theoretical preconceptions have shown that the impact of COVID on the financial system passes through several channels linked to uncertainty and loss of income. Following old and recent work (Carrera and Lanteri, 2007;Ramayandi, 2011;Fornari and Stracca, 2013;Caldara et al, 2016;Vinus and Kusairi, 2017;Boissay et al, 2020;Zabai, 2020;, we use an econometric framework of autoregressive vector Bayesian to quantify the impact of COVID-19 on the financial system. We estimate the model using the monthly series from December 2013 to Oct. 2020.…”
Section: Covid-19 Pandemicmentioning
confidence: 99%